Alluvial sedimentology and geomorphology of a cut and fill sequence on the Dassieboskloof River, Wuppertal, Southwestern Cape - Shaw, Arabel C (Department of Environmental and Geographical Science, 2024)
The unique and well preserved fluvial sequences within the valleys of the Cederberg Mountains of the Western Cape, South Africa, provide the opportunity for palaeoenvironmental reconstruction which will add to the sparse evidence from across southern Africa. The location of the study site at the edge of two physio-climatic zones provides insight into the controversy surrounding the characteristics of Late Quaternary environments in this semi-arid winter rainfall region. It is already accepted that the southwestern Cape behaved out of phase with the rest of southern Africa during Quaternary climatic fluctuations and resulted in significantly different environmental conditions. The discovery of an extensive sedimentary sequence south of Wuppertal in the northern Cederberg on the Dassiebosldoof River provides colluvium package overlain by a laminated and interbedded fluvial sedimentary package approximately eight metres thick, demonstrating a change in conditions from deposition to incision ( cut-and-fill). Physical, geochemical and mineralogical analysis is used to characterise the sediments as well as mapping and ground trothing of the contemporary fluvial dynamics across a portion of the Moordenaarsgat River and eastward draining Tra-Tra River; a detailed investigation of the depositional environment will expand the palaeoenvironmental record for the region, and the two adjacent climatic zones (Cederberg and arid Karoo). This research will contribute to a more detailed understanding of geomorphology in the northern Cederberg and the driving mechanisms, which are extremely significant when assessing and managing potential future aridification and its impact on this fragile landscape.